Closed (St-Closed) Compressible Modules and Closed (St-Closed) Retractable Modules - Al Hakeem, Mohammed Baqer Hashim; Al-Mothafar, Nuhad S. (Iraqi Journal of Science, 2024)
Let  be a commutative ring with 1 and  be a left unitary R-module. In this paper, we give a generalization for the notions of compressible (retractable) module. As well as, we study closed (St-closed) compressible and closed (St-closed) retractable. Furthermore, some of their advantages, properties, categorizations and instances have been given. Finally, we study the relation between them.